Reliable and efficient hop-by-hop flow control. - Özveren, Cüneyt (Computer communication review.)
Hop-by-hop flow control can be used to fairly share the bandwidth of a network among competing flows. No data is lost even in overload conditions; yet each flow gets access to the maximum throughput when the network is lightly loaded. However, some schemes for hop-by-hop flow control require too much memory; some of them are not resilient to errors. We propose a scheme for making hop-by-hop flow control resilient and show that it has advantages over schemes proposed by Kung. We also describe a novel method for sharing the available buffers among the flows on a link; our scheme allows us to potentially reduce the memory requirement (or increase the number of flows that can be supported) by an order of magnitude. Most of the work is described in the context of an ATM network that uses credit based flow control. However our ideas extend to networks in which flows can be distinguished, and to rate based flow control schemes.